Development Of Prevention Module For Sexual Behavior In Adolescents - Wae, Rahmawati; Chandra, Yasrial (Educational Guidance and Counseling Development Journal, 2025)
One of the things that causes a teenager to engage in premarital sexual behavior is a lack of knowledge and understanding about reproductive health. A module is a medium that contains material that can be used as a guide in understanding and obtaining information about reproductive health. This research aims to develop a prevention module for adolescent premarital sexual behavior. This type of research is the development (research & development) of the ADDIE model. Through this research, a valid module was successfully developed (feasibility value 85.5). It is hoped that the module that has been developed can be used to prevent premarital sexual behavior among teenagers